Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Semangat Kerja Karyawan - Astrawan, I Nyoman; Putri Trarintya, Mirah Ayu; Putra Astawa, I Putu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study aims to partially and simultaneously influence compensation and work environment on employee morale at the Guwang Traditional Village LPD. The population in this study were all 32 employees of the Guwang Traditional Village LPD. Determination of the sample using a saturated sample, so that the entire population is used as a sample. After testing the instrument and testing the classical assumptions, then the data was analyzed using multiple linear regression analysis. The results of the analysis show that compensation has a positive and significant effect on the morale of the employees of the Guwang Traditional Village LPD. The work environment has a positive and significant effect on the morale of the Guwang Traditional Village LPD employees. Compensation and work environment simultaneously have a positive and significant effect on the morale of the Guwang Traditional Village LPD employees. Suggestions that can be put forward in this study are that it is suggested to the Guwang Traditional Village LPD to pay more attention to the employee salary system and to increase air circulation in the employee’s work space such as adding windows or marketing air conditioners so that the work space is more comfortable for employees so that employee morale is increasing.